Design and synthesis of a novel series of non-nucleoside HIV-1 inhibitors bearing pyrimidine and N-substituted aromatic piperazine. Issue 22 (1st December 2018) - Jin, KaiJun; Sang, YaLi; De Clercq, Erik; Pannecouque, Christophe; Meng, Ge
Graphical abstract: Highlights: Twenty-six new compounds were designed, synthesized and evaluated for their in vitro anti-HIV activity. Five compounds exhibited good potency with EC50(IIIB) values against wild-type HIV-1. Molecule docking studies were also carried out to illustrate structure-affinity relationships of these compounds. Abstract: A novel series of substituted piperazine-1-yl-pyrimidine derivatives were designed and synthesized as a new type of HIV-1 non-nucleoside inhibitors. Various N -substituted aromatic groups were incorporated into the piperazine ring through a simple and practical route to investigate the biological activity of these target compounds against wild-type and resistant strains of HIV-1. All of the target compounds were also evaluated as HIV-1 reverse transcriptase inhibitors in MT-4 cell cultures. The biological results showed that six of these compounds displayed inhibitory activities against the wild-type strain, among of which7q and7t were found to be the two most active analogues possessing EC50 values of 31.50 μM and 3.36 μM, respectively. Molecular modeling studies of7q provide valuable information for developing new anti-HIV-1 inhibitors.